Dominant factors affecting uterine prolapse in Dr. Moewardi Hospital, Surakarta, in 2013-2015 - Asih Anggraeni; Vitri Wulansari; Darto Darto (Universitas Airlangga, 2017)
Objectives: To determine the dominant factors that affected uterine prolapse at Dr. Moewardi General Hospital Surakarta.Materials and Methods: This study was conducted to 259 cases of uterine prolapse at Dr. Moewardi Hospital, Surakarta, in the periods of January - December in the years 2013-2015. This was a correlational quantitative analytic study using chi-square test and regression analysis.Results: Factors affecting uterine prolapse were parity (p=0.024), age (p=0.036) and occupation (p=0.039). Parity had the highest regression analysis result of 0.145 with probability of uterine prolapse in those with parity >2 in this study was 2.753 times higher than in those with parity ≤2.Conclusion: Factors that had been proved to have significant effect on uterine prolapse were age, occupation, and parity. Parity was the predominant factor in affecting uterine prolapse in Dr. Moewardi Hospital, Surakarta.